Business Environment Uncertainty’s Effect On The Performance Of Three Stars Hotels And Below In Saudi Arabia: The Mediating Role Of Competitive Advantage - Ali M, Alsubaihi Ibrahim (2024)
Despite the rising demand and occupancy rates in Saudi Arabia's hotel industry, the sector faces significant performance challenges due to intensified competition and supply dynamics. The proliferation of small and medium-sized accommodations has compelled hotel managers and owners to adopt competitive strategies to navigate environmental uncertainties successfully. This is particularly crucial in today's global context, where uncertainties have become prevalent across various domains of life, including the hospitality sector. This study examines the relationship between environmental uncertainty and hotel performance within the context of small and medium-sized hotels in Saudi Arabia, focusing on how competitive advantage acts as a mediator in this relationship. The study encompassed five major regions in Saudi Arabia: Mecca, Medina, Riyadh, the Eastern border, and Jazan. Employing a quantitative approach, the instrument of survey form was used to targeted group of top management personnel and accommodation owners with a sample size of 375 respondents. Data was collected through an online questionnaire survey distributed via email to identified hotels. The study garnered a substantial response, with 238 usable responses. The data was meticulously analysed using statistical tools such as SPSS and SmartPLS 3.2.1. The study's key findings unveiled a strong and significant relationship between market uncertainty, technology uncertainty, competitive uncertainty, competitive advantage, and hotel performance.